2019
DOI: 10.17058/reci.v9i2.12099
|View full text |Cite
|
Sign up to set email alerts
|

A segurança do paciente no contexto das flebites notificadas em um hospital universitário

Abstract: Justificativa e Objetivos:A flebite pode levar à necessidade de intervenções assistenciais de maior complexidade, como a utilização de antibioticoterapia ou até uma intervenção cirúrgica, além de prolongar a internação do paciente e aumentar o custo e risco de infecções. O presente estudo visa descrever as flebites notificadas em um hospital universitário e assim contribuir com possíveis ações de melhoria na qualidade do cuidado e na segurança do paciente. Métodos:Estudo observacional de c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 20 publications
0
4
0
2
Order By: Relevance
“…An association was observed with the study ( 9 ) that demonstrated that the administration of Amoxicillin-Potassium Clavulanate resulted in greater potential for the development of phlebitis. It should be noted that the fact that Amoxicillin-Potassium Clavulanate presented a pH between 8.0 and 10 may have increased the risk for the occurrence of chemical phlebitis ( 22 , 25 ) . Other authors state that antibiotics with similar characteristics were considered a risk factor for the development of this event ( 3 , 9 , 12 , 25 ) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An association was observed with the study ( 9 ) that demonstrated that the administration of Amoxicillin-Potassium Clavulanate resulted in greater potential for the development of phlebitis. It should be noted that the fact that Amoxicillin-Potassium Clavulanate presented a pH between 8.0 and 10 may have increased the risk for the occurrence of chemical phlebitis ( 22 , 25 ) . Other authors state that antibiotics with similar characteristics were considered a risk factor for the development of this event ( 3 , 9 , 12 , 25 ) .…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that the fact that Amoxicillin-Potassium Clavulanate presented a pH between 8.0 and 10 may have increased the risk for the occurrence of chemical phlebitis ( 22 , 25 ) . Other authors state that antibiotics with similar characteristics were considered a risk factor for the development of this event ( 3 , 9 , 12 , 25 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Guiding patients and family members on signs and symptoms of phlebitis, during infusion and post-infusion after extraction of PVC [2,31]. Educating patients on the fact that ensuring proper care of PVC helps reduce risk of infection [17].…”
mentioning
confidence: 99%
“…Previously identifying comorbidities such as diabetes mellitus due to the changes in the circulatory system caused by this disease [31].…”
mentioning
confidence: 99%
“…Estudo observacional retrospectivo, realizado em unidades de internação de pacientes adultos, ressalta o momento da ocorrência de flebites com prevalência da administração dos antibióticos (46,1%), antieméticos (25%) e analgésicos não opioides (20%) na terapia intravenosa periférica. 21 Pesquisa observacional apresenta similaridade com a presente investigação quanto ao uso de medicamentos na terapia por hipodermóclise, sendo os analgésicos e antibioticoterápicos os mais prevalentes (ambos com 30%), e as medicações mais empregadas nos pacientes em uso de hipodermóclise foram a dipirona, morfina, ondansetrona e dexametasona, respectivamente. 17 Ainda, outra investigação observacional prospectiva encontrou como medicamentos mais infundidos na hipodermóclise a morfina, a dipirona e a escopolamina.…”
Section: Discussionunclassified